Chemical Constitute and Larvicidal Activity of Fractions of Ajuga chamaecistus tomentella Plant against Malaria Vector Anopheles stephensi - Mahnaz Khanavi; Behnaz Najafi; Seyede Nargess Sadati; Mohammad Reza Abai; Hassan Vatandoost (Tehran University of Medical Sciences, 2017)
Backgrand: The genus Ajuga, belongs to Lamiaceae family, is one of the exclusive subspecies in the flora of Iran. The plants of this genus are used traditionally for treatment of joints pain, gout, jaundice, and as insecticide. Methods: larvicidal activity of methanol 80% extract and partition fractions of hexane, chloroform, and ethyl acetate obtained from aerial parts of Ajuga chamaecistus subspecies tomentella against malaria vector An. stephensi was evaluated. Phytochemical study of active fraction was analyzed using column chromatography and spectroscopy. Results: According to the results, among different fractions, hexane fraction has the most larvicidal activity with mortality rate of 100% in concentration of 102 ppm and LC50 of 95.66ppm. The structure of compound 1, main phytoecdysteroid compound separated from hexane fraction, was determined to be ajugalide-E. Conclusion: The results suggested that the hexane fraction of Ajuga chamaecistus subsp tomentella could be used as a natural and biodegradable insecticide.